TEKNIK KOMUNIKASI GURU DAN SISWA DALAM PENINGKATAN PRESTASI SISWA - Nasor, M. (Universitas Islam Negeri Raden Intan Lampung, 2014)
Communicating is the foundation of education.Without communication, ideas, directions, andthoughts are lost or misunderstood. Students may notunderstand teaching material, educators may notunderstand directions given to them, and teachers maynot understand that a gap in communication isforming. So teacher student communication plays abig part in the success of classroom interaction.According to Cooper, effective teachers shoulddemonstrate competencies in sending and receivingmessages that give or obtain information, express orrespond to feelings, speculate or theorize, maintainsocial relationships and facilitate interaction, and seekto convince or influence. Beyond these competencies,several teacher communication behaviors andstrategies must be learned to enhance student learning.What teachers need to know obviously goes beyondhow to enhance self-presentation, how to keepstudents on task, and how to manage studentresistance. Effective communication includes muchmore than simple knowledge transmission. This articlewill discusses somethings related to teacher studentcommunication.